A legal perspective of tourism as an impetus for socio-economic transformation in South Africa - Mogale, Patrick Tseliso (My University, 2019)
This mini-dissertation articulates the socio-economic challenges faced by South Africans, such as poverty, unemployment and lack of infrastructural development. The mini- dissertation establishes that tourism is an engine that drives socioeconomic transformation thus elimination poverty, creating employment and bringing about infrastructural development. It highlights tourism law, policies and international instruments that ensure that factors such as environmental protection, travelling, skills development, and so on ensure that tourism is promoted and thrives to transform the lives of historically disadvantaged South Africans. It identifies tourism impediments that stand as obstacles hindering tourism to provide socio-economic transformation and makes a moderate attempt to offer sustainable solutions. It recommends that the Department of Tourism through co-operative governance with other organs of state should strengthen implementation of legislation, institutions and policies vested within its power to ensure that tourism is developed to create employment and alleviate poverty. As a comparative analysis the approaches of Australia and Canada were utilised and useful lessons were drawn from them.
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2019
Keywords: Poverty alleviation; Employment; Conservation; Infrastructural development; Socio-economic transformation; Tourism -- Law and legislation -- South Africa; Public welfare -- Law and legislation -- South Africa; Law and economic development